Increased CDC6 Expression Associates With Poor Prognosis in Patients With Clear Cell Renal Cell Carcinoma - Yao, Yicong; Wang, Yi; Wu, Denglong; Hu, Baoying (Frontiers in Oncology, 2021)
Backgrounds:CDC6 (Cell division control protein 6), located at chromosome 17q21.3, plays a regulatory role in the early stage of DNA replication and has unique functions in various malignant tumors. Here, we evaluate the relationship between CDC6 expression and oncology outcomes in patients with clear cell renal cell carcinoma (ccRCC). Methods: A retrospective analysis of 118 ccRCC patients in Affiliated Hospital of Nantong University from 2015 to 2017 was performed. Create tissue microarrays (TMA) in triplicate from formalin-fixed and paraffin-embedded specimens. Immunohistochemistry (IHC) was performed, and the relationship between CDC6 expression and standard pathological features and prognosis was evaluated. Obtain the RNA sequencing data and corresponding clinical information from the Cancer Genome Atlas (TCGA) database. Use Gene Set Enrichment Analysis (GSEA) to identify signal pathways related to CDC6. Perform Univariate and multivariate Cox regression analysis to evaluate independent prognostic factors. In addition, the relationship between CDC6 and immunity was also investigated. Results: The results of IHC staining showed that CDC6 in ccRCC tissue was obviously up-regulated compared with adjacent normal kidney tissue. Univariate and multivariate Cox regression analysis determined CDC6 as an independent prognostic factor (both P<0.05). GSEA showed that the high expression of CDC6 was related to Cell cycle, Chemokine signaling pathway, Cytosolic DNA sensing pathway, JAK_STAT signaling pathway, Nod like receptor signaling pathway, P53 signaling pathway, Toll like receptor signaling pathway etc. As for immunity, it was also related to tumor mutational burden (TMB), immune checkpoint molecules, tumor microenvironment and immune infiltration. Conclusions: CDC6 expression has been identified as an independent poor prognostic factor of OS. Increased expression of CDC6 is a potential independent poor prognostic factor of OS in ccRCC patients.